1975
DOI: 10.1080/03014467500000851
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on morphological characteristics

Abstract: Study has been made of 37 anthropometric measurements in a socially selected sample of 125 Belgian families, comprising parents and adult children. The parent-child and mid-parent-child correlation coefficients indicate that the extent of genetic determination varies considerably from one measurement to another, being greatest in the longitudinal body measurements, least in the circumferences involving soft tissues and in measures of the nose and mouth. Further analysis of the intrafamilial correlation, and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
4
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 3 publications
9
69
4
2
Order By: Relevance
“…For example, culturally associated selection pressures such as chewing habits, food types, and food preparation methods may exert significant effect on dentition including occlusion (Corruccini 1984;Sharma and Susanne 1991). However, the general trend in the heritability patterns observed in this study is in agreement with the findings of Nakata et al (1974), Susanne (1975), and Devor et al (1986aDevor et al ( , 1986b, who found similar observations that bony measures have higher heritabilities than soft tissue measures among different human populations.…”
Section: Discussionsupporting
confidence: 73%
“…For example, culturally associated selection pressures such as chewing habits, food types, and food preparation methods may exert significant effect on dentition including occlusion (Corruccini 1984;Sharma and Susanne 1991). However, the general trend in the heritability patterns observed in this study is in agreement with the findings of Nakata et al (1974), Susanne (1975), and Devor et al (1986aDevor et al ( , 1986b, who found similar observations that bony measures have higher heritabilities than soft tissue measures among different human populations.…”
Section: Discussionsupporting
confidence: 73%
“…Familial aggregation offatness relative to other anthropometries Body dimensions reflecting soft tissue tend to have lower heritabilities than those of skeletal size (Vandenberg, 1962;Susanne, 1975;Mueller, 1977). To what extent is this consistent with respect to fat measurements?…”
Section: Familial Aggregationmentioning
confidence: 99%
“…This meant that the fatness variable studied must at least be some indirect Brook et al (1975), Osborne and DeGeorge (1959), Vandenberg (1962) Adoption and Biron et al (1977), Bouchard et al (1982), Garn et al (1976aGarn et al ( ,b, 1977aGarn et al ( .b, 1979a, Hartz cohabitation et al (1977), Shenker et al (1974), Withers (1964) Familial Bayley (1954), Borjeson (1962Borjeson ( , 1964, Bouchard (1980), Bouchard et al (1980a,b), Bowles aggregation (1932), Garn et al (1975), Garn and Clark (1975), Hawk and Brook (1979), Hewitt (1957), Howells (1966), Little and Malina (unpublished data), Martin et al (1973), Matsuki and Yoda (1971), McHenry and Giles (1971), Mueller (1977Mueller ( ,1978, Mueller and Titcomb (1977), Mueller and Reid (1979), Mueller and Malina (1980), Reynolds (1951), Savard et al (1983), Susanne (1975), Tanner and Israelsohn (1963), Wolanski (1976) (weight adjusted for height, body mass index, skinfold, somatotype, etc.) or direct (e.g., body density) measure of body fatness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that facial features are inherited from the parent generation. Genetic studies have reported a heritable component in the facial anthropometry of twins, as well as other family members (Susanne, 1975;Byard et al, 1985;Hauspie et al, 1985). Various face-related measurements have also been reported to display heritability, with values ranging from 0.25 to 0.61 (Raposo-do-Amaral et al, 1989;Arya et al, 2002;Ermakov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%